Growth performance of critically endangered Hypselobarbus pulchellus in biofloc system: Influence of carbon sources on immune response, enzyme and antioxidant activity - Anantharaja, Kanagaraja; Barlaya, Gangadhar; C. H. Raghavendra; B. S. Anand Kumar; G. M. Siddaiah; Radhakrishnan , Kalidoss; Chadha , N. K.; Krishna , Gopal; Routray , P.; Hemaprasanth, K. P. (Indian Journal of Fisheries, 2024)
We investigated the effect of various carbon sources on the production performance of critically endangered Hypselobarbus pulchellus in biofloc system. The experimental setup comprised four biofloc treatment groups with various carbon sources (jaggery, tapioca, rice and corn flour) and a control group. Healthy early fry (0.0068 g) was randomly stocked at 100 individuals per m3 into 15 circular fibre reinforced plastic (FRP) tanks (1000 l) and raised for 90 days. All the tested carbon sources significantly influenced weight gain, weight gain (%) and specific growth rate (SGR), with the jaggery treatment displaying the best growth performance (p0.05). Compared to the control, the biofloc groups had significantly lower concentrations of nitrogen compounds, specifically total ammonia nitrogen, nitrite and nitrate concentrations were significantly lowered (0.29, 0.35 and 1.32 mg l-1, respectively) in jaggery treatment (p